Minimal acupuncture is not a valid placebo control in randomised controlled trials of acupuncture: a physiologist's perspective - Lundeberg Thomas; Näslund Jan; Lund Iréne (BMC, 2009)
Abstract Placebo-control of acupuncture is used to evaluate and distinguish between the specific effects and the non-specific ones. During 'true' acupuncture treatment in general, the needles are inserted into acupoints and stimulated until deqi is evoked. In contrast, during placebo acupuncture, the needles are inserted into non-acupoints and/or superficially (so-called minimal acupuncture). A sham acupuncture needle with a blunt tip may be used in placebo acupuncture. Both minimal acupuncture and the placebo acupuncture with the sham acupuncture needle touching the skin would evoke activity in cutaneous afferent nerves. This afferent nerve activity has pronounced effects on the functional connectivity in the brain resulting in a 'limbic touch response'. Clinical studies showed that both acupuncture and minimal acupuncture procedures induced significant alleviation of migraine and that both procedures were equally effective. In other conditions such as low back pain and knee osteoarthritis, acupuncture was found to be more potent than minimal acupuncture and conventional non-acupuncture treatment. It is probable that the responses to 'true' acupuncture and minimal acupuncture are dependent on the aetiology of the pain. Furthermore, patients and healthy individuals may have different responses. In this paper, we argue that minimal acupuncture is not valid as an inert placebo-control despite its conceptual brilliance.